PENINGKATAN PEMAHAMAN HUKUM TENTANG KEKERASAN SEKSUAL PADA SISWA SMA DI KECAMATAN KONDA KABUPATEN KONAWE SELATAN - La Ode Muhamad Sulihin; Guasman Tatawu; Lade Sirjon; Jabalnur Jabalnur; Ali Rizky (LPPM Universitas Bina Bangsa, 2024)
The high cases of sexual violence against children in South Konawe Regency have become a concern for various parties. Although physical sexual violence appears on the surface, non-physical sexual violence is still rife, especially in the school environment. The students were unaware that they were either perpetrators or victims of non-physical sexual violence. In the view of the students, non-physical sexual violence behavior is only a joke, but in the perspective of criminal law, the behavior is a criminal offense. Therefore, it is necessary to increase legal understanding to students related to sexual violence. This legal counseling is carried out at MAN 1 Konsel and SMAN 8 Konsel with direct legal counseling methods in the form of lectures and discussions. Through this service activity, the students learned about the criminal law regulations related to sexual violence. With that understanding, students understand that non-physical sexual violence is prohibited in criminal law and is threatened with criminal sanctions. The results of this legal counseling illustrate the leap in knowledge gained by students. With an understanding of criminal law regulations this will help in creating thoughts, behaviors based on legal norms